Klasifikasi Jenis Buah Pisang Menggunakan Algoritma Convolutional Neural Network - Fadila Huda; M. Pajar Kharisma Putra (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
This research aims to address challenges in classifying types of banana using the Convolutional Neural Network (CNN) algorithm. The research background reflects the need for an automatic classification system to enhance the efficiency of banana farmers, considering that the manual methods still widely used have weaknesses in consistency and accuracy. Previous studies have successfully employed CNN for classifying various objects, including fruits. The CNN method is implemented using the VGG16 model training approach and prepared training data. This study focuses on three types of bananas—male, "kepok," and "muli"—with a specific emphasis on seed classification. Testing evaluates the model's accuracy, revealing a 78% accuracy rate. The application of the CNN algorithm can improve efficiency in classifying banana types. Despite achieving a 78% accuracy rate, the test results also indicate good values for precision (81%) and recall (78%). Therefore, the CNN algorithm can be considered an effective solution for automatically addressing issues in classifying banana types, contributing positively to banana farmers' productivity in Indonesia, especially when examining Accuracy, Precision, and Recall in percentage form.